A comparison of the local structure in ball-milled and hand ground skutterudite samples using EXAFS. (August 2015) - Short, M.; Bridges, F.; Keiber, T.; Rogl, G.; Rogl, P.
Abstract: Skutterudites are considered to be good thermoelectrics with high figures of merit, ZT . After synthesis, electrodes are created by grinding and hot pressing the resulting powder. Materials such as NdFe4 Sb12 exhibit a significantly greater figure of merit, ZT, (about 43%) when it is ball milled to produce fine powders (inital powder 160 nm; after hot pressing ∼330 nm). This enhancement is typically attributed to the reduced particle size, which in turn decreases the mean free path of phonons, and consequently decreases the thermal conductivity. This work aims to investigate whether there is any damage to the crystal structure in the particles formed by ball milling, which could also affect its thermal conductivity. Using a temperature dependent, Extended X-ray Absorption Fine Structure (EXAFS) analysis of a hand ground and ball milled sample of the skutterudite Ndy Fe4 Sb12, we have determined that ball milling causes no significant damage to the local structure around any site. Consequently further improvements in ZT may be possible with smaller particles. Highlights: Can increase ZT; e.g. by 43% (from 0.74 to 1.06) using ball-milled small particles. Local structure (via EXAFS) is the same in balled-milled and hand ground material. No evidence for any amorphous fraction in the ball-milled material. Suggests further improvements feasible, using much smaller particle sizes.